Physical Internet – a Novel Application Area for Industry 4.0 - Puskás, Eszter; Bohács, Gábor (International Journal of Engineering and Management Sciences, 2019)
The Physical Internet (PI or π) is one of the most decisive ideas for future logistics systems. The idea behind it is to implement logistic systems which apply the principles of Internet information flow. Simultaneously technological innovations of Industry 4.0 have also appeared. Our current research deals with the applicability of the tools of Industry 4.0 technology in the PI system. Following the literature review we analyse the individual technological tools that could improve the functioning of PI components. Subsequently we will detail the usability of a specific Industry 4.0 tool and finally determine the future research steps.